Proceedings of the 7th Annual Conference on Innovation and Technology in Computer Science Education 2002
DOI: 10.1145/544414.544461
|View full text |Cite
|
Sign up to set email alerts
|

Reducing abstraction level when learning computability theory concepts

Abstract: The paper illustrates how theories from mathematics education can be applied for explaining student conception of computing science ideas. It does this by demonstrating how the theme of reducing abstraction [5] can be used for analyzing students' mental processes when the students are in the process of solving problems in Computability Theory. The topic of Computability Theory in presented here as an example for demonstrating how research in Computing Science education can use learning theories, "borrowed" fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 6 publications
1
61
0
9
Order By: Relevance
“…One might ask why it is acceptable to omit the step involving division of a polynomial as implicit but important to have commutativity of multiplication explicit. One interpretation is that, as Hazzan (1999) notes, commutativity is an issue that may only become explicitly a focus of attention when encountering abstract algebra for the first time, so it is important that students can demonstrate that they know when it does and does not apply, while division by a (non-zero) polynomial is more peripheral to the study of group theory.…”
Section: Final Analysis Of the Proofmentioning
confidence: 99%
“…One might ask why it is acceptable to omit the step involving division of a polynomial as implicit but important to have commutativity of multiplication explicit. One interpretation is that, as Hazzan (1999) notes, commutativity is an issue that may only become explicitly a focus of attention when encountering abstract algebra for the first time, so it is important that students can demonstrate that they know when it does and does not apply, while division by a (non-zero) polynomial is more peripheral to the study of group theory.…”
Section: Final Analysis Of the Proofmentioning
confidence: 99%
“…This is discussed in [Hazzan, 1999]. Example 6 One metaphor for the real line is that it is a set of points (as in Example 3.)…”
Section: Examplementioning
confidence: 99%
“…Mathematical concepts in abstract algebra are related to topological concepts and various studies have been carried about abstract algebra (e.g., Clark et al, 1999;Hazzan, 1999). Clark et al (1999) examined students' attitudes toward abstract algebra course.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that although abstract algebra was a difficult course, students desired group activities and computer-aid learning environment. Abstract algebra concepts are mostly difficult to understand, reducing abstraction-a way of understanding abstract topics-helps students to understand algebra concepts simply (Hazzan, 1999). Hazzan (1999) investigated undergraduate students' reducing abstraction level while learning abstract algebra concepts.…”
Section: Introductionmentioning
confidence: 99%